Dillenia suffruticosa exhibited antioxidant and cytotoxic activity through induction of apoptosis and G2/M cell cycle arrest - Armania N.; Yazan L.S.; Musa S.N.; Ismail I.S.; Foo J.B.; Chan K.W.; Noreen H.; Hisyam A.H.; Zulfahmi S.; Ismail M. (2024)
Indexed by Scopus